Alterations in the subcellular distribution of NADPH oxidase p47(phox) in hypothalamic paraventricular neurons following slow pressor Angiotensin II hypertension in female mice with accelerated ovarian failure - Van Kempen, Tracey A. (J Comp Neurol, 2015)
At younger ages, women have a lower risk for hypertension than men, but this sexual dimorphism declines with the onset of menopause. These differences are paralleled in rodents following “slow-pressor” angiotensin II (AngII) administration: young male and aged female mice, but not young females, develop hypertension. There is also an established sexual dimorphism both in the cardiovascular response to the neurohypophyseal hormone arginine vasopressin (AVP) and in the expression of oxidative stress. We examined the relationship between AngII-mediated hypertension and the cellular distribution of the superoxide generating NADPH oxidase (NOX) in AVP-expressing hypothalamic paraventricular nucleus (PVN) neurons in “menopausal” female mice. Dual labeling immunoelectron microscopy was used to determine if the subcellular distribution of the organizer/adapter NOX p47(phox) subunit is altered in PVN dendrites following AngII administered (14 days) during the “postmenopausal” stage of accelerated ovarian failure (AOF) in young female mice treated with 4-vinylcyclohexene diepoxide. Slow-pressor AngII elevated blood pressure in AOF females and induced a significant a significant increase in near plasmalemmal p47(phox) and a decrease in cytoplasmic p47(phox) in PVN AVP dendrites. These changes are opposite to those observed in AngII-induced hypertensive male mice (Coleman et al., J. Neuroscience 33: 4308-16, 2013), and may be ascribed in part to baseline differences between young females and males in the near plasmalemmal p47(phox) on AVP dendrites seen in the present study. These findings highlight fundamental differences in the neural substrates of oxidative stress in the PVN associated with AngII hypertension in postmenopausal females compared with males.